The Orphan Nuclear Receptor SHP Inhibits Hepatocyte Nuclear Factor 4 and Retinoid X Receptor Transactivation: Two Mechanisms for Repression - Lee, Yoon-Kwang (American Society for Microbiology, 2000)
The orphan nuclear hormone receptor SHP interacts with a number of other nuclear hormone receptors and inhibits their transcriptional activity. Several mechanisms have been suggested to account for this inhibition. Here we show that SHP inhibits transactivation by the orphan receptor hepatocyte nuclear factor 4 (HNF-4) and the retinoid X receptor (RXR) by at least two mechanisms. SHP interacts with the same HNF-4 surface recognized by transcriptional coactivators and competes with them for binding in vivo. The minimal SHP sequences previously found to be required for interaction with other receptors are sufficient for interaction with HNF-4, although deletion results indicate that additional C-terminal sequences are necessary for full binding and coactivator competition. These additional sequences include those associated with direct transcriptional repressor activity of SHP. SHP also competes with coactivators for binding to ligand-activated RXR, and based on the ligand-dependent interaction with other nuclear receptors, it is likely that coactivator competition is a general feature of SHP-mediated repression. The minimal receptor interaction domain of SHP is sufficient for full interaction with RXR, as previously described. This domain is also sufficient for full coactivator competition. Functionally, however, full inhibition of RXR transactivation requires the presence of the C-terminal repressor domain, with only weak inhibition associated with this receptor interaction domain. Overall, these results suggest that SHP represses nuclear hormone receptor-mediated transactivation via two separate steps: first by competition with coactivators and then by direct effects of its transcriptional repressor function.